The Tromsø Nappe Contact with the Nakkedal Nappe Complex NE of Tromsdalstind : Shear kinematics and relationship with metamorphism. - Indrevær, Kjetil (Universitetet i Tromsø, 2011)
The tectonic contact between the Nakkedal Nappe Complex and the Tromsø Nappe crops out NE of Tromsdalstind, 5 km E of Tromsø, Norway. Petrological- and structural analysis of the contact have been undertaken in order to contribute to a better understanding of the tectonometamorphic history of the Uppermost Allochton in the Scandianavian Caledonides. Methods such as P-T pseudosection analysis, Computer-Integrated Polarization microscopy (CIP) and quartz grain size and -shape analysis have been combined with classic polarizing microscopy to obtain shear sense, P-T-conditions, flow stress and strain rate of deformation. A minimum P-T condition of a Scandian prograde metamorphism is obtained from a metapelite in the Tromsø Nappe at 0.9 GPa and 680°C. A widespread distribution of quartz deformation microstructures indicate that deformation was continuous and took place over a large span of temperatures during final retrograde conditions from more than 700°C to less than 400°C. Flow stress and strain rate during deformation are estimated to ~30 MPa and 10-11 s-1. Chessboard patterns in quartz are observed locally and c-axis orientation images and pole figures of a quartz vein within the Tromsø Nappe show prism [c]- and basal -slip indicative c-axis preferred orientions (CPOs) in completely recrystallized grains. Prism [c]- and basal -slip pole figures from the same microstructure have previously only been reported in large submagmatic quartz grains. The implications of the new findings for the current theories on the development of prism [c]-slip are discussed. A new unit within the Skattøra Migmatite Complex (SMC) is identified and evidence of retro-eclogites and partial melting in the Tromsø Nappe is presented. A switch in the direction of nappe translation during a late- to post-Scandian retrograde metamorphism from either SW or NE to SSE is identified in the Tromsø Nappe. The results are set into context with previous work in the area and it is concluded that the Tromsø Nappe was subjected to at least two major ...